Tourism and agrotourism evolution on an European and national level - Eugenia-Dorina Ciobanu; Manea Drăghici (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 8th Edition of the International Symposium, November 2017, Bucharest, 2017)
In this article we wanted to identify, analyze and present the evolution in the last years of the tourism and agrotourism on an European and national level. In order to do that, the following indicators have been analyzed: the evolution and structure of international arrivals of tourists around the globe, the evolution and structure of international tourism encash, the evolution and share of tourist accommodation in Romania, the evolution and share of the accomodation capacity in Romania, the evolution of arrivals in accomodation units from Romania and the evolution of overnight stays in accomodation units from Romania. Following this analysis that is presented in the article in the rows below, we come to the conclusion that the tourism and agrotourism, on an European and national level, has had a constant growth in the last 5 years, thus representing an important branch with possibilities to develop economy, generating profit.
Keywords: Q11; 330; tourism; agrotourism; boarding